William B. Allen journal - Allen, William B., active 1853-1855.
Volume containing a memorandum of incidents of a cruise to China and Japan aboard the U.S. sloop-of-war Vandalia.
Collection material in English.
Keywords: Vandalia (Sloop); Ship's papers -- 19th century; China -- Description and travel; Japan -- Description and travel